Pricing strategy and buyer's considerations for house: Central government area vs tourism centre area - Renna Magdalena; Oliandes Sondakh (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
The purpose of this study is to propose Pricing Strategy. First, this study determines the dominant factors that influence the number of housing prices in Denpasar as the Capital city of Bali Island, a center of tourism in Indonesia and Jakarta as the Capital City and central government of Indonesia. This study uses a multiple linear regression test; the sample was 115 houses data, 60 houses in Denpasar, and 55 in Jakarta. Second, this study will propose a strategy for determining house prices. The survey results will show what factors are dominant in determining the number of housing prices in Denpasar and Jakarta. This research is helpful for home sellers to determine the cost of the house to be sold. This research is also helpful for prospective home buyers to determine the reasonableness of the house price they will buy. This study also covers the discussion regarding the consideration of homebuyers in terms of taxes.